2014
DOI: 10.1039/c4cc02466d
|View full text |Cite
|
Sign up to set email alerts
|

An expedient approach to pyrrolo[3,2-c]quinolines via regioselective formation of the pyrrole nucleus over indoles

Abstract: An efficient approach for the synthesis of pyrrolo[3,2-c]quinolines (the core nucleus of the natural product martinellic acid) from protected 2-alkynylanilines via the regioselective formation of pyrroles followed by Heck and intramolecular Michael addition has been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…But when homopropargyl aminesubstituted aniline 5a was tested for the formation of α-iodoketone, surprisingly only iodocyclized product was observed in 68% yield (Scheme 4). The product 6a was the same as reported in our previous iodocyclization study with molecular iodine 7 and no α-iodoketone product was observed.…”
Section: Syn Thesissupporting
confidence: 84%
“…But when homopropargyl aminesubstituted aniline 5a was tested for the formation of α-iodoketone, surprisingly only iodocyclized product was observed in 68% yield (Scheme 4). The product 6a was the same as reported in our previous iodocyclization study with molecular iodine 7 and no α-iodoketone product was observed.…”
Section: Syn Thesissupporting
confidence: 84%
“…The required alkynes were prepared in high yields following our previously reported procedure, by palladium/copper catalysed Sonogashira reaction under mild reaction conditions. 4 The electrophilic cyclization of alkyne 1a (Scheme 1) was initiated with K 2 CO 3 as the base and I 2 as the electrophilic source. However, the reaction failed to give the hoped-for products 2a and/or 3a (Scheme 1), changing the reaction conditions and using different bases and solvents led to the same results.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported recently the selective formation of a pyrrole nucleus over indole by taking advantage of two competing amine nucleophiles in the electrophilic cyclization of alkynes; this was achieved by modifying the electronic properties of one of the amine groups and hence manipulating its nucleophilic attack. 4 The present study highlights an efficient and simple approach for the regio-selective synthesis of iodocyclized dihydrofurans from alkynes bearing two different competing nucleophiles i.e. amine and alcohol.…”
Section: Introductionmentioning
confidence: 94%
“…4‐Bromo and 4‐methoxybenzaldehyde gave the highest yield of the corresponding products, while aliphatic aldehydes resulted in the minor amount of products [90] . This reaction was also catalyzed by N ‐methyl‐2‐pyrrolidone in alkaline medium to achieve same products in good to high yields (60‐85%) [91] …”
Section: ‐Alkynylanilines In the Synthesis Of Six‐membered Heterocycl...mentioning
confidence: 96%
“…[90] This reaction was also catalyzed by N-methyl-2-pyrrolidone in alkaline medium to achieve same products in good to high yields (60-85%). [91] A gold-catalyzed approach for the synthesis of 11Hindolo[3,2-c]quinoline structures 119 was achieved by treating 2-[2-(2-aminophenyl)ethynyl]anilines 116 with various aldehydes. Due to the formation of complex form of 116 with [Au], the reaction is progressed by cyclization/aromatization of substrate to give indole 117, followed by Pictet-Spengler [92] imination/cyclization reaction/aromatization of the latter (Scheme 36).…”
Section: -Alkynylanilines In the Synthesis Of Six-membered Heterocycl...mentioning
confidence: 99%